Changement climatique et conflits de genre dans l’agriculture paysanne dans l’Ouest Cameroun : cas de Batcham - Dany Franck A. Tiwa (VertigO)
In the Batcham subdivision family farms are ruled by a former land tenure that organizes the relationship of household members to the land. This reduces conflicts to a minimum threshold. To men belong property rights materialized by perennial crops and to women belong culture of food rights, both inalienable. For more than a decade, unprecedented climatic disturbances are jeopardizing these secular equilibrium. To reduce their dependency to cycle of rains now unpredictable, women farmers are strongly coveting bottomlands dominated by plants of raffia-palms that are exploited by men for the production of palm wine. The analysis of women's logic of action in the light of the scarcity and/or abundance of resources theory, suggest that beyond the need to adapt to changing climate conditions, there is a growing challenge to male privilege and, therefore, to the patriarchal nature of the Batcham society. Through semi-structured and informal interviews, we have been able to identify the terms that take this competition around the land and the resources that both men and women mobilize to alienate these bottomlands. The analysis of the logics of action of women in this changing climate context demonstrates a growing challenge to male privilege and therefore to the patriarchal organization of this society. The palm wine, main victim of this belligerence, is rooted in local culture where it is subject to multiple uses. Its disappearance would have serious economic and socio-cultural consequences.